El Tromen: El desafío de conservar sus aves acuáticas - Di Martino, Sebastián; Freire, Rodolfo; Gómez, Jorge; Moronell, Virginia (Revista Aves Argentinas, 2008)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).